IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH DI PONDOK PESANTREN TARBIYAH ISLAMIYAH PARIANGAN - Mulyadi Mulyadi (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
The purpose of this study was to determine the steps undertaken by the Implementing Regulation BS Pariangan TI MPMBS and find constraints - the constraints faced in the implementation OF MPMBS Boarding School Pariangan Tarbiyah Islamiyah. Research methods that researchers use qualitative date collection techniques, ( 1 ) observation, ( 2 ) interviews, and ( 3 ) study the documentation. The date were then analyzed in a way , data reduction, Presentation date, and giving a conclusion. The conclusion ofthis study isnecessaryactive role of allcomponentsthe existingat boarding schools. MPMBSImplementationcan be doneas expectedby theBoarding School. This studyalsogivesgreat meaningthatactiverole ofthe perpetratorsMPMBSat boarding schooland the allocation ofsufficientfunds, willbeimplementingMPMBSsuccess ofin theschoolandin theBoarding School.Key Words: Implementasi, Manajemen peningkatan mutu